Clinical pharmacist‐led costs optimization in ischaemic stroke care: A diagnosis‐related groups‐based intervention study - Li, Yun; Li, Xianlin; Guo, Haitao; Zhang, Jin; Zheng, Xiaojun (British journal of clinical pharmacology, 2025)
This study aimed to evaluate the impact of clinical pharmacists' intervention on drug cost optimization for ischaemic stroke inpatients under the diagnosis-related groups (DRGs) payment model. This study collected hospitalization data of patients with ischaemic stroke in the BR23 disease group from the neurology department between June 2023 and July 2024. The dataset was divided into a control group (no pharmacist intervention) and an experimental group (pharmacist intervention). Using t-tests, chi-square tests and Mann-Whitney U tests, this study analysed the changing trends in hospitalization costs for ischaemic stroke patients after pharmacists participated in clinical pharmacy pathways under the DRG model. The analysis included demographic characteristics, comorbidities, length of hospitalization, incidence of adverse drug reactions, irrational medication use rates, total hospitalization costs, total drug costs and costs of key monitoring drugs between the 2 groups. There were no significant differences in age, sex, or comorbidities. Length of hospitalization and incidence of adverse drug reactions did not differ significantly (P > .05), but irrational medication use was lower in the experimental group (P < .05). Compared to the control group, the experimental group had significantly lower total hospitalization costs, total drug costs and costs of key monitoring drugs (P < .05), along with clear improvements in cost control and excess payment management. This study demonstrates that pharmacist involvement in clinical pathways under the DRGs payment model effectively reduces drug costs for hospitalized ischaemic stroke patients while ensuring clinical efficacy and safety, highlighting the role of pharmacists in cost control.